PENGARUH KONFLIK KERJA, BEBAN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP TINGKAT STRES PADA PEGAWAI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN LABUHANBATU - Mayanti, Riska; Nasution, Ade Parlaungan; Syahputra, Rizki (JURNAL MANAJEMEN AKUNTANSI (JUMSI), 2021)
In this study using a sample of 63 employees, the type of data and data sources used in this study using primary and secondary data. The instrument test to test the appropriateness of the statement is the validity test and reliability test. The data analysis method used in this study is multiple regression analysis. . The results showed that the first hypothesis is known that the t-count of the work conflict variable is 1.183 with a sig value of 0.241. If tcount <ttable value (1.183 <1.670) with a significance of 0.241 greater than 0.05, then H0 is accepted and H1 is rejected. Thus it can be concluded that partially work conflict has no positive and insignificant effect on stress levels. The second hypothesis is that the t-count value of the workload variable is 2.759 with a sig value of 0.008. If the value of tcount> ttable value (2.759> 1.670) with a significance of 0.008 greater than 0.05 then H1 is rejected and H0 is accepted. Thus it can be concluded that partially workload has a positive and significant effect on stress levels. The third hypothesis, it is known that the tcount value of the work environment variable is 4,946 with a sig value of 0,000. If the value of tcount> ttable value (4,946> 1,670) with a significance of 0,000 is greater than 0.05, then H1 is rejected and H0 is accepted. Thus it can be concluded that partially the work environment has a positive and significant effect on stress levels. The fourth hypothesis, it is known that the t-count value of the work motivation variable is 2.759 with a sig value of 0.008. If the value of tcount> ttable value (2.759> 1.670) with a significance of 0.008 greater than 0.05 then H1 is rejected and H0 is accepted. Thus it can be concluded that partially work motivation has a positive and significant effect on stress levels. The fifth hypothesis is known that the value of Fcount> Ftable value (15.413> 2.53) at significance (0.000 <0.05). In other words, work conflict, workload and work environment variables simultaneously have a positive and very significant effect on stress levels.